(untitled) (diségno, 2018)
The book by Vito Cardone Gaspard Monge, padre dell’ingegnere contemporaneo, published in 2017 by DEI Tipografia del Genio Civile, deals with the precious cultural heritage that the French scientist has passed on to our days. This legacy must be extended not only to the formulation of the rules of descriptive geometry, but also to the study plan designed to train engineers; because, as the author states: “its effectiveness and farsightedness are evident, indeed, after more than two hundred years, it still permeates most of the schools for engineers around the world, whose choices are within the criteria and problems already identified at that time” (read more).